Antiproliferative and Immunoregulatory Effects of Azelaic Acid Against Acute Myeloid Leukemia via the Activation of Notch Signaling Pathway - Dongdong, Zhang; Jin, Yanxia; Yang, Tian; Yang, Qian; Wu, Balu; Chen, Yanling; Luo, Ziyi; Liang, Li; Liu, Yunjiao; Xu, Anjie; Tong, Xiqin; Can, Can; et al. (Frontiers in Pharmacology, 2019)
Acute myeloid leukemia (AML) had a poor prognosis and high incidence of relapse due to the therapeutic resistance. Azelaic acid (AZA) is a small molecular compound which exhibited antitumor effect. In this study, we report AZA can inhibit the proliferation of AML cells, laser confocal microscopy showed AZA-treated AML cells began to develop swelling and cytoplasmic vacuolization. Furthermore, AZA promotes the proliferation of NK and T cells and increases the secretion of TNF-α and IFN-γ, it also increases the expression levels of CD107a and TRAIL in NK cells and CD25 and CD69 in T cells to influence the activation and cytotoxic ability. AZA-treated NK cells can kill the AML cells more efficiently at the single-cell level observed under the micro-fluidic chips. Further mechanistic analysis using protein mass spectrometry analysis and Notch signaling reporter assay demonstrated that Notch1, Notch2 were up-regulated and the Notch signaling pathway was activated. Moreover, combination AZA with Notch inhibitor RO4929097 decreased the expression of Notch1, Notch2 and downstream HES1 and HEY1, made AML cells insensitive to AZA-induced apoptosis and alleviated AZA-mediated cytotoxicity in AML. In vivo, AZA relieves the leukemic spleen infiltration and extends the survival, the percentage of CD3-CD56+ NK cells and CD4+CD8+ T cells as well as the secretion of cytotoxic cytokines are increased after the treatment of AZA. Our findings establish that AZA as a potential Notch agonist against AML by regulating the Notch signaling pathway.